Application of an Efficient Enhancer in Gene Function Research - Feng-Xian Guo; Rui-Xue Yang; Xia Yang; Jing Liu; Yin-Zheng Wang (Plants, 2024)
Although great progress has been made in transgenic technology, increasing the expression level and thus promising the expected phenotypes of exogenous genes in transgenic plants is still a crucial task for genetic transformation and crop engineering. Here, we conducted a comparative study of the enhancing efficiency of three putative translational enhancers, including Ω (natural leader from a plant virus), OsADH 5′ (natural leader from a plant gene), and ARC (active ribosomal RNA complementary), using the transient gene expression systems of Nicotiana benthamiana and Chirita pumila. We demonstrate that three tandem repeats of ARC (3 × ARC) are more efficient than other enhancers in expression. The enhancing efficiency of 6 × ARC is further increased, up to 130 times the expression level without the insertion of enhancers. We further evaluated the enhancing efficiency of 6 × ARC under agrobacterium-mediated transformation systems. In C. pumila, 6 × ARC significantly amplifies the phenotypic effect of CpCYC1 and CpCYC2 in repressing stamen development and yellow pigmentation. In Arabidopsis thaliana, 6 × ARC and the AtAP1 promoter work together to promote the accumulation of anthocyanin pigments in vegetative and reproductive organs. Most significantly, the fusion of 6 × ARC in a CpCYC1/2 transgenic system in C. pumila fully reveals that these genes have the complete function of repressing the yellow spots, displaying an advantage in manifesting the function of exogenous genes. This study highlights the application potential of the enhancer 6 × ARC in gene function research in plants.